Child-Friendly Education: Fostering Mathematical Communication in Primary School Children - Novitasari, Meggy; Sumardjoko, Bambang; Pramono, Suwito Eko; ., Wasino (Journal of Ecohumanism, 2024)
Child-friendly education has a high urgency in developing students' mathematical communication in primary schools. Child-friendly education creates a learning environment of holistic development, communication in social interaction. The research objectives in this article are twofold. First, to describe the learning process of mathematics in child-friendly education in primary schools. Second, to explore the growth and development of mathematics communication in child-friendly education in primary schools. The overall research type is research and development. The research type of this article is qualitative case study. Data collection was by interview, observation and document analysis. The researcher was present as the key instrument. Data validity, triangulation of sources and methods. Data analysis cyclical flow model and constant comparison. Research results; 1) Child-friendly education provides opportunities for fun learning, development and prosperity. The research school provides a) hands-on learning experiences, b) constructive activities, and c) space for growth. Maths learning in child-friendly education goes through three stages. Providing opportunities for learners to utilise physical and non-physical facilities. 2) Mathematics learning in child-friendly education at the research schools fostered all aspects of mathematical communication. Horizontal communication development, average 34.74 to 48.87. Vertical communication development, average 33.78 to 63.83. Oral communication growth, average 33.70 to 52.43. Growth and development of written communication, average 33.70 to 49.61. Growth and development of integrative communication, average 33.83 to 53.35.